(untitled) (AYUSHDHARA, 2022)
Diabetes Mellitus is a metabolic disorder associated with multisystem complications. The prevalence and incidences of the both types of diabetes are significantly increased over the past two decades. The recently published ICMR-INDIAB national study reported that there are 62.4 million people with type 2 diabetes mellitus and 77 million people with prediabetes in India. These numbers are projected to increase to 101 million by the year 2030 due to changed of life style of the people all over the world. Habits of sedentary life, having a lot of fast foods and improper follow of diet habits are the main causes to develop Diabetes mellitus. It can be correlated with Madhumeha in Ayurveda. A 45 years old female patient treated in the OPD of Central Ayurveda Research Institute, Guwahati from 23rd Sept. 2020 with a complain of generalised weakness, weight loss, increase amount of urination and attraction of ant towards the excreted urine for 9 months. Examination, laboratory investigations and history leads to diabetes mellitus. Different Ayurvedic herbomineral drugs which were mentioned in different texts were given to the patient. It shows the effective results in the management of Madhumeha (Diabetes mellitus).